SPREADSHEET BASED BUSINESS DECISION MAKING SYSTEM (CASE STUDY IN BONOROWO LAND, LAREN, LAMONGAN) - Desrina Yusi Irawati; David Andrian; Albertus Daru Dewantoro (Spektrum Industri, 2020)
Bonorowo land in Laren Subdistricts, Lamongan Districts, is one of the areas that uses its land for rice, corn and kenaf cultivation. The agricultural sector in Laren does not yet have a detailed economic analysis. Farmers ignore the importance of considering initial capital and some â€œsmallâ€ costs in this activities. Therefore, in this study, the calculation of business feasibility was carried out on rice, kenaf, and corn farmer groups in Bonorowo land, West Laren. Business feasibility analysis is conducted through calculation of the value of NPV, IRR, and IP. The calculation system uses a Microsoft Excel spreadsheet formula. The NPV, IRR, and PI values of corn cultivation are Rp. 524,182.40; 144.43%; and 2,9. The NPV, IRR, and PI values for kenaf cultivation are Rp. 1,145,532.39; 266.43%; and 5.15. The NPV, IRR, and PI values for rice cultivation are Rp. -495,085.78; -25.18%; and -0.79. The results of the economic analysis of the cultivation of rice, corn, and kenaf in Bonorowo land, Laren Subdistrict, show that rice cultivation has caused losses and is not feasible to continue.